Ecological Zoning of Guadalupe Cuautepec, San Juan Bautista Suchitepec, Oaxaca, from a technical and community perspective - Álvarez-Olguín, Gabriela; Sustaita-Rivera, Fidencio; Bautista-Sánchez, Gilberto; Pedro-Santos, Eucebio César (Instituto de Ecología, A.C., 2016)
In the Guadalupe Cuautepec community, deforestation, overgrazing and unsustainable agricultural practices, have caused soil erosion and hence the siltation of the lagoon located in the town. In order to generate basic information to create protective strategies to this water body, an ecological zoning was developed from the diagnosis of this community resources’: water, soil and vegetation. From the technical point of view a socioeconomic and biophysical characterization was performed; the latter included geomorphological, hydrologic, geological, soil, vegetation, erosion, potential land use, land use conflicts and ground instability. On the other hand, a participatory rural appraisal was conducted, in which the most relevant problems related to natural resources and the community actions needed for the sustainable management of such resources were identified. Top priority targets were set to achieve sustainable management of natural resources, among which are: soil conservation works, controlled logging activities and reforestation of non-vegetated areas. It was estimated that 77.8% of the Cuautepec territory presents high and very high risk of erosion, with indices above than 50 t/ha/ year. It was determined that the most eroded lands in need of restoration cover 609.34 ha, and that the priority area to reforest is 439.52 ha.